A semiotic-pedagogic framework for the design of a virtual museum of Byzantine art - Voutounos, Chrysanthos; Lanitis, Andreas (My University, 2012)
This paper presents the semiotic-pedagogic framework which assists the design of a virtual museum of Byzantine art. The proposal explains how the framework helps the design process by clarifying issues around the multifaceted problems concerning the knowledge required to use technology for educational purposes and the interpretation of signs and sign processes. The framework takes into consideration the affinity of important principles from cultural semiotics and semiotic aesthetic theories with Vygotsky’s “signs” and “tools” and the symbolic function of Byzantine art.
Keywords: Semiotics; Pedagogy; Virtual Museum; Byzantine art; Culture